GERAKAN DAKWAH KOMUNITAS GENERASI MILENIAL DAN HARMONISASI KEHIDUPAN BERAGAMA DI KOTA BANDUNG: STUDI KASUS PADA KOMUNITAS SHAB AL-QO - Juju Saepudin; Neneng Habibah (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
This articles provides the result of study on Religious Education in the community Shab Alqo in Bandung City. This theme was necessarily studied since many religious-based communities of millennial generation were indicated to be infiltrated by extremist—in a term of religious understanding—which caused disharmony among religious people. This study was a descriptive study with qualitative approach. The data collection techniques of this study included observation, interview and literature study on the documents related to the theme of study. The data were then analyzed inductively and resulted in some conclusions, namely: First, the motive of hijrah in the community Shab Alqo was a regret of past story and a hope of better life in the future. Second, the da’wah style in Shab Alqo was a direct communication with the members, even though it commonly used online or social media. Third, the topics or the massages of da’wah delivered to the members were Islamic topics from al-Qur’an and al-Hadits, which was designed with tahsin and tafsir program and other program adjusted to the need and condition of the members. Fourth, the obstacle of this community was the lack of religious teachers who could put all efforts to share the knowledge and experience to the members on this da’wah.